Implementasi Pembelajaran Saintifik Berbasis Keterampilan Belajar Dan Berinovasi 4C Terhadap Hasil Belajar IPA Dengan Kovariabel Sikap Ilmiah Pada Peserta Didik - Ni Nyoman Lisna Handayani (Purwadita : Jurnal Agama dan Budaya, 2020)
In detail, the purpose of this study can be elaborated as follows: (1) To determine the effect of the implementation of scientific learning based on learning skills and 4C innovation on the learning outcomes of Natural Sciences in class V students of SD Cluster 15 Buleleng District. (2). To determine the effect of the implementation of scientific learning based on learning skills and 4C innovation on the learning outcomes of science in class V students of Elementary School Cluster 15 Buleleng District, after scientific attitudes are controlled. (3). To find out how much a significant contribution to scientific attitudes towards learning outcomes of science students. This research is an experimental research. The research design used in this study is the Single Factor Independent Groups Design With Use Of Covariate. The multiple choice test method is used to collect data about the science learning outcomes of students, while the non-test method in the form of a questionnaire is used to collect data on scientific attitudes of students. Keywords: Scientific learning based on learning skills, 4C, science learning outcomes